A Linguistic Analysis of Verbal Humor Found in the Transcription of Animated TV Series Gravity Falls - Silvia Nurfajri Aprilla Wananda (VELES Voices of English Language Education Society, 2021)
This paper explores the analysis of verbal humours found in the transcription of animated TV series, Gravity Falls. This paper aims to find out what types of verbal humour found in the transcription of animated TV series Gravity Falls and to find out how the verbal humour found in the transcription of animated TV series ‘Gravity Falls’analyses linguistically by using General Theory of Verbal Humour (GTVH). The study found that there are 29 verbal humours in the object of the research which categorized into 9 out of 12 categories. The verbal humours found before are analysed linguistically by applying the six Knowledge Resources in the General Theory of Verbal Humour (GTVH); Script Opposition (SO), Logical Mechanism (LM), Situation (SI), Target (TA), Narrative Strategy (NS), and Language (LA). The analysis is done in a hierarchical order of the KRs to analyse the verbal humour.